Environmental Justice: The Influence of Environmental Ethics, Environmental Knowledge on Waste Management with Religiosity as a Mediation Variable - Susminingsih Susminingsih; Ahmad Rosyid; Muhammad Nasrullah; Junaeti Junaeti; Siti Aminah Caniago (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2025)
This article examine how environmental knowledge, religiosity, environmental ethics, and behavioral influence waste management behavior and realization of environmental justice among batik MSME actors in Indonesia. This research is a field study employing quantitative methods, involving 232 respondents selected through purposive and accidental sampling techniques. The collected data analysed using the PLS-SEM method. This study concluded that environmental knowledge and religiosity are serious challenges in efforts to form environmental justice, MSME actors can feel the impact of their business so they care about industrial waste management, environmental ethics strengthen the commitment of MSME actors to nature conservation programs and prevent environmental damage, internalisation of environmental ethics values which in line with religiosity is more effective in encouraging fair waste management behaviour than just increasing environmental knowledge, and encouragement of waste management is evidence of good interaction between humans and nature. Keywords: environmental justice; environmental ethics; environmental knowledge; waste management; religiosity   Abstrak Artikel ini mengkaji bagaimana pengetahuan dan etika lingkungan, religiositas, dan faktor perilaku mempengaruhi perilaku pengelolaan limbah serta perwujudan keadilan lingkungan di kalangan pelaku UMKM batik di Indonesia. Penelitian ini merupakan studi lapangan dengan pendekatan kuantitatif yang melibatkan 232 responden, yang dipilih melalui teknik purposive dan accidental sampling. Data dianalisis menggunakan metode PLS-SEM. Penelitian menyimpulkan bahwa pengetahuan lingkungan dan religiositas masih menjadi problem dalam membentuk keadilan lingkungan, pelaku UMKM dapat merasakan dampak dari aktivitas usahanya sehingga mendorong kepedulian terhadap pengelolaan limbah industri, etika lingkungan memperkuat komitmen pelaku UMKM terhadap pelestarian dan pencegahan kerusakan lingkungan, internalisasi nilai-nilai etika lingkungan yang selaras dengan religiositas lebih efektif dalam mendorong perilaku pengelolaan limbah yang adil dibandingkan sekadar peningkatan pengetahuan lingkungan, dan dorongan terhadap pengelolaan limbah merupakan bukti adanya interaksi yang baik antara manusia dan alam.  Kata Kunci: keadilan lingkungan; etika lingkungan; pengetahuan lingkungan; pengelolaan limbah; religiositas